A ceramic toughened light-weight iron-based alloy and a preparation method and application thereof
By adding nano-AlN ceramic particles to iron-based alloys and using vacuum sintering and melting technology, ceramic-toughened lightweight iron-based alloys were prepared, solving the problem of insufficient strength and plasticity at high temperatures, achieving a balance between strength and plasticity, and expanding their application in high-power diesel engine parts.
Patent Information
- Application Number
- CN202410053801.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-15
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-01-15
AI Technical Summary
Existing iron-based alloys lack sufficient strength and plasticity at high temperatures. In particular, the strength and plasticity of gray cast iron and vermicular graphite cast iron decrease significantly above 400°C, making it difficult to meet the requirements for use at higher temperatures. Furthermore, ceramic particles are easily contaminated and poorly dispersed in the alloy.
Nanoscale AlN ceramic particles were used as the reinforcing phase. The AlN/Al master alloy ingot was prepared by mixing in a zirconia ball mill and sintering under vacuum conditions without pressure. This avoided direct contact between the nanoscale AlN ceramic particles and the high-temperature Fe solution. Combined with vacuum arc melting furnace melting, ceramic toughened lightweight iron-based alloy was prepared.
It significantly improves the room temperature and high temperature mechanical properties of ceramic-toughened lightweight iron-based alloys, achieves a good match between strength and plasticity, solves the problem of insufficient strength and plasticity of existing iron-based alloys at high temperatures, and expands their application in high-power diesel engine parts.
Smart Images

Figure CN117867400B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite materials technology, and in particular to a ceramic-toughened lightweight iron-based alloy, its preparation method, and its application. Background Technology
[0002] Increased power density means higher operating temperatures and pressures in the combustion chamber. Currently, the cylinder head fire surface temperature of high-power-density diesel engines (105 kW / L) under development even reaches 600°C, while the fire surface temperature of cylinder heads for engines exceeding 88 kW / L surpasses 100°C. This places higher demands on the cylinder head material's stable mechanical properties and excellent high-temperature durability across a wide temperature range. Furthermore, for cylinder head (structural component) materials, high elongation, strength-ductility product, and yield strength ratio are crucial indicators for ensuring service safety, while meeting service performance requirements. Therefore, developing materials that balance high strength, good ductility, and stable performance across a wide temperature range is particularly important.
[0003] Currently, iron-based alloys used in cylinder heads mainly include gray cast iron and vermicular graphite cast iron. Both gray cast iron and vermicular graphite cast iron suffer from a significant reduction in high-temperature mechanical properties, especially above 400℃, where their strength and plasticity are very low, making it difficult to meet the requirements for use at higher temperatures. Furthermore, gray cast iron and vermicular graphite cast iron also have problems such as low elongation, yield strength ratio, and strength-ductility product at various temperatures, making them prone to cracking and failure during service, thus limiting their further application in the field of cylinder head components for higher power density diesel engines.
[0004] Lightweight iron-based alloys refer to alloys with iron as the base material and other alloying elements added. Under the influence of these alloying elements, iron-based alloys typically possess high strength, corrosion resistance, and high-temperature resistance. Furthermore, their production cost is relatively low, allowing for further applications in the field of cylinder head components for higher power-density diesel engines. However, lightweight iron-based alloys have slightly lower ductility and toughness, which limits their further applications; therefore, strengthening of lightweight iron-based alloys is necessary.
[0005] In existing technologies, strengthening methods for iron-based alloys include solid solution strengthening, deformation strengthening, precipitation strengthening, dispersion strengthening, and grain refinement strengthening. Among these, dispersion strengthening is a method with a significant strengthening effect and shows great promise. The second phase in dispersion strengthening is generally a high-melting-point oxide, carbide, or nitride, which allows the strengthening effect to be maintained at high temperatures. Ceramic particles are corrosion-resistant, resistant to high-temperature oxidation, and have good high-temperature stability, therefore they are often used as the second phase in metal matrix composites during dispersion strengthening. Common methods for adding ceramic particles during dispersion strengthening include external addition (direct addition of ceramic particle powder) and in-situ internal generation (in-situ internal generation of ceramic particles). Direct addition of ceramic particle powder requires consideration of the wettability and interface issues between the ceramic particles and the metal, and the particle surface is easily contaminated, affecting particle dispersion and thus the strengthening effect. In-situ internal generation of ceramic particles can avoid the surface contamination problem of externally added particles to a certain extent and has better dispersibility, but the generation of other phases is inevitable during the process of self-generating the ceramic phase, making it difficult to control the content of the ceramic phase, and the presence of other phases can also affect the performance of the composite material to some extent. Summary of the Invention
[0006] Based on this, it is necessary to provide a ceramic-toughened lightweight iron-based alloy, its preparation method, and its application to address the above-mentioned technical problems. The obtained ceramic-toughened lightweight iron-based alloy has both high strength and ductility, and its preparation method does not suffer from the problems of ceramic particle contamination and difficulty in controlling the ceramic phase content.
[0007] In a first aspect, the present invention provides a ceramic-toughened lightweight iron-based alloy, wherein the raw materials for synthesis are composed of the following components by mass percentage: Mn: 25%, Al: 9%, Ni: 8%, C: 1%, Ti: 0.2%, AlN: 0.1% to 1%, with the balance being Fe and unavoidable impurities.
[0008] Furthermore, the synthetic raw materials consist of the following components by mass percentage: Mn: 25%, Al: 9%, Ni: 8%, C: 1%, Ti: 0.2%, AlN: 0.5%, with the balance being Fe and unavoidable impurities.
[0009] Secondly, the present invention provides a method for preparing a ceramic-toughened lightweight iron-based alloy, comprising the following steps:
[0010] S1: Preparation of AlN / Al intermediate alloy composite powder;
[0011] S2: The AlN / Al master alloy composite powder is loaded into a graphite mold and sintered in a hot-press sintering furnace without pressure. After sintering and cooling to room temperature, it is taken out and cut into blocks to obtain AlN / Al master alloy ingots.
[0012] S3: Pure iron millimeter ingots with a purity ≥99%, Fe-50Mn centimeter ingots, pure aluminum millimeter ingots, pure nickel millimeter ingots, Fe-5C centimeter ingots, pure titanium millimeter ingots, and AlN / Al master alloy ingots are batched into alloy blocks according to a mass ratio of 11.80~12.55:50:0~6.75:8:20:0.2:2.5~10 and placed in the first crucible station of the vacuum arc melting furnace. Then, sponge titanium is placed in the second crucible station of the vacuum arc melting furnace.
[0013] S4: Vacuum the vacuum arc melting furnace and fill it with argon gas. First, melt the sponge titanium, and then repeatedly melt the prepared alloy block 10 times before taking it out to obtain a ceramic-toughened lightweight iron-based alloy.
[0014] Furthermore, the preparation of AlN / Al master alloy composite powder includes:
[0015] S11: Weigh a mixed powder consisting of nano AlN powder with a mass of M1 and Al powder with a mass of 9M1, and methanol with a mass of 0.5M1, and place it into a zirconia ball mill jar.
[0016] S12: Add 3mm, 5mm and 8mm zirconia grinding balls to the zirconia grinding jar respectively, wherein the total mass of the zirconia grinding balls is 30M1, and the mass ratio of 3mm, 5mm and 8mm zirconia grinding balls is 2:2:1;
[0017] S13: After sealing the zirconia ball mill jar with an O-ring, the zirconia ball mill jar is evacuated and filled with argon gas. The mixture is ball-milled at a speed of 150 r / min for 3 hours to obtain a uniformly mixed AlN / Al master alloy composite powder.
[0018] Furthermore, when the AlN / Al master alloy composite powder is loaded into a graphite mold and sintered in a hot pressing sintering furnace, it is a vacuum pressureless sintering process. The sintering process is automatically heated from room temperature to 520°C, and the heating current is 0.25KA.
[0019] The sintering vacuum degree is 3Pa~4Pa. The automatic heating process is as follows: from room temperature to 100℃, the heating rate is 3℃ / min; from 100℃ to 400℃, the heating rate is 10℃ / min; from 400℃ to 480℃, the heating rate is 5℃ / min; from 480℃ to 520℃, the heating rate is 2℃ / min; and the temperature is held at 520℃ for 60min.
[0020] The AlN / Al master alloy ingot is 5mm × 5mm × 3mm in size.
[0021] Furthermore, evacuating and purging the vacuum arc melting furnace with argon gas includes the following steps:
[0022] The mechanical pump and pre-evacuation valve of the vacuum arc melting furnace are turned on to evacuate the vacuum. When the vacuum level of the vacuum arc melting furnace drops to 5 Pa, the fore-stage valve, main evacuation valve, and molecular pump of the vacuum arc melting furnace are turned on in sequence to carry out the high vacuum process, and the vacuum level reaches 3.0 × 10⁻⁶ Pa. -3 When Pa is reached, shut off the molecular pump and the main extraction valve;
[0023] Open the charging valve to charge argon gas into the furnace. When the vacuum degree of the vacuum arc melting furnace is -0.07MPa, close the charging valve.
[0024] Furthermore, in step S4, the process of melting the prepared alloy block each time involves moving the arc gun to the melting position, and after successful arc ignition, gradually increasing the arc gun current by 50A each time, up to 550A. After all the ingredients have completely melted, the electromagnetic stirrer is turned on and stirred for 5 minutes. Then, the arc gun current is slowly and gradually reduced until it is turned off.
[0025] Thirdly, this invention provides an application of the above-mentioned ceramic-toughened lightweight iron-based alloy or the ceramic-toughened lightweight iron-based alloy prepared by the above-mentioned preparation method in a diesel engine. The beneficial effects of this invention are:
[0026] (1) The ceramic-toughened lightweight iron-based alloy of the present invention significantly improves the room temperature and high temperature mechanical properties of the ceramic-toughened lightweight iron-based alloy by adding nano-sized AlN ceramic particles.
[0027] (2) The method for preparing ceramic toughened lightweight iron-based alloy of the present invention involves mixing nano-AlN powder and Al powder in a zirconia ball mill jar and then performing pressureless sintering under vacuum conditions to prepare an AlN / Al master alloy ingot. In this ingot, nano-AlN is encapsulated by Al. When smelting with other ingredients, nano-AlN will not come into direct contact with the high-temperature Fe solution, and the nano-AlN ceramic particles will not be contaminated, thus not affecting the dispersibility of the nano-AlN ceramic particles. In addition, the fact that nano-AlN will not come into direct contact with the high-temperature Fe solution can also avoid the formation of other phases during the smelting process. Attached Figure Description
[0028] Figure 1 This is a schematic flowchart of the preparation method of ceramic-toughened lightweight iron-based alloy in an embodiment of the present invention.
[0029] Figure 2 The XRD patterns of the ceramic-toughened lightweight iron-based alloys prepared in Examples 1-4 and the iron-based alloy prepared in Comparative Example 1 are shown.
[0030] Figure 3 This is a schematic diagram of the microstructure of an iron-based alloy under an optical microscope, provided in an embodiment of the present invention. Figure 3(a) The microstructure of the iron-based alloy prepared in Comparative Example 1 under a 200x optical microscope. Figure 3 (b) The microstructure of the ceramic-toughened lightweight iron-based alloy prepared in Example 2 under a 200x optical microscope;
[0031] Figure 4 This is a schematic diagram showing the microstructure and diffraction spot calibration results of the ceramic-toughened lightweight iron-based alloy prepared in Example 2 under a transmission electron microscope. Figure 4 (a) is a schematic diagram of the diffraction spot calibration results of the austenitic phase. Figure 4 (b) is a schematic diagram of the diffraction spot calibration results for the ferrite phase. Figure 4 (c) is a schematic diagram of the diffraction spot calibration results of the TiC phase. Figure 4 (d) is a schematic diagram of the diffraction spot calibration results of the AlN phase;
[0032] Figure 5 The figures show the tensile stress-strain curves at different temperatures of the ceramic-toughened lightweight iron-based alloys prepared in Examples 1-4 and the iron-based alloy prepared in Comparative Example 1. Figure 5 (a) is a tensile stress-strain curve at room temperature. Figure 5 (b) is a tensile stress-strain curve at 400℃. Figure 5 (c) is the tensile stress-strain curve at 600℃. Detailed Implementation
[0033] To facilitate understanding of the present invention, a more complete description will be given below with reference to the accompanying drawings. Preferred embodiments of the invention are shown in the drawings. However, the invention can be implemented in many different forms and is not limited to the embodiments described herein.
[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.
[0035] Currently, the iron-based alloys used in cylinder heads mainly include gray cast iron and vermicular graphite cast iron, as shown in Table 1. Table 1 shows the variation of mechanical properties of cylinder head materials with temperature. Gray cast iron and vermicular graphite cast iron exhibit a significant decrease in mechanical strength at high temperatures, especially above 400℃, where their strength and plasticity are very low, making it difficult to meet the requirements for use at higher temperatures.
[0036] Table 1. Variation of mechanical properties of cylinder head materials with temperature
[0037]
[0038] Lightweight iron-based alloys do not experience a significant decrease in mechanical strength at high temperatures, but their ductility and toughness are slightly lower, requiring strengthening.
[0039] The ceramic-toughened lightweight iron-based alloy prepared using nano-sized AlN ceramic particles in this invention has significantly improved room temperature and high temperature mechanical properties, and can greatly improve plasticity without sacrificing strength.
[0040] In one embodiment, the ceramic-toughened lightweight iron-based alloy is composed of the following components by mass percentage: Mn: 25%, Al: 9%, Ni: 8%, C: 1%, Ti: 0.2%, AlN: 0.1% to 1%, with the balance being Fe and unavoidable impurities.
[0041] Nano-AlN belongs to the hexagonal crystal system. It has low density, high strength, no melting point or softening point, good thermal stability, and excellent thermal, electrical, mechanical and chemical properties. It is a ceramic reinforcing phase with excellent comprehensive performance. By adding nano-sized AlN ceramic particles, the mechanical properties of ceramic-toughened lightweight iron-based alloys are significantly improved at room temperature and high temperature.
[0042] In a preferred embodiment, the synthetic raw materials consist of the following components by mass percentage: Mn: 25%, Al: 9%, Ni: 8%, C: 1%, Ti: 0.2%, AlN: 0.5%, with the balance being Fe and unavoidable impurities.
[0043] In one embodiment, the preparation method for the above-mentioned ceramic-toughened lightweight iron-based alloy includes the following steps:
[0044] S1: Preparation of AlN / Al master alloy composite powder.
[0045] Specifically, the preparation of AlN / Al master alloy composite powder includes:
[0046] S11: Weigh a mixture of nano-AlN powder (mass M1) and Al powder (mass 9M1) and methanol (mass 0.5M1) and place them into a zirconia ball mill jar.
[0047] S12: Add 3mm, 5mm and 8mm zirconia grinding balls to the zirconia grinding jar respectively, wherein the total mass of the zirconia grinding balls is 30M1, and the mass ratio of the 3mm, 5mm and 8mm zirconia grinding balls is 2:2:1.
[0048] S13: After sealing the zirconia ball mill jar with an O-ring, the zirconia ball mill jar is evacuated and filled with argon gas. The mixture is ball-milled at a speed of 150 r / min for 3 hours to obtain a uniformly mixed AlN / Al master alloy composite powder.
[0049] S2: The AlN / Al master alloy composite powder is loaded into a graphite mold and sintered in a hot pressing sintering furnace. After sintering and cooling to room temperature, it is taken out and cut into blocks to obtain AlN / Al master alloy ingots.
[0050] Specifically, when the AlN / Al master alloy composite powder is loaded into a graphite mold and sintered in a hot pressing sintering furnace, it is a vacuum pressureless sintering process. The sintering process is automatically heated from room temperature to 520°C, and the heating current is 0.25KA.
[0051] The sintering vacuum degree is 3Pa to 4Pa. The automatic heating process is as follows: from room temperature to 100℃, the heating rate is 3℃ / min; from 100℃ to 400℃, the heating rate is 10℃ / min; from 400℃ to 480℃, the heating rate is 5℃ / min; from 480℃ to 520℃, the heating rate is 2℃ / min; and the temperature is held at 520℃ for 60 minutes. The size of the AlN / Al master alloy ingot is 5mm × 5mm × 3mm.
[0052] Nano-AlN powder and Al powder were mixed in a zirconia ball mill and then sintered under vacuum conditions to prepare an AlN / Al master alloy ingot. In this ingot, the nano-AlN is encapsulated by Al. When smelting with other ingredients, the nano-AlN will not come into direct contact with the high-temperature Fe solution, and the nano-AlN ceramic particles will not be contaminated or have their dispersibility affected. In addition, the fact that the nano-AlN does not come into direct contact with the high-temperature Fe solution can also avoid the formation of other phases during the smelting process.
[0053] S3: Pure iron millimeter ingots with a purity ≥99%, Fe-50Mn centimeter ingots, pure aluminum millimeter ingots, pure nickel millimeter ingots, Fe-5C centimeter ingots, pure titanium millimeter ingots, and AlN / Al master alloy ingots are batched into alloy blocks according to a mass ratio of 11.80~12.55:50:0~6.75:8:20:0.2:2.5~10 and placed in the first crucible station of the vacuum arc melting furnace. Then, sponge titanium is placed in the second crucible station of the vacuum arc melting furnace.
[0054] It should be noted that the vacuum arc melting furnace includes multiple crucible stations. The prepared alloy blocks need to be placed in different crucible stations from the sponge titanium. The purpose of melting the sponge titanium first is to consume the remaining oxygen in the vacuum melting furnace and prevent it from being oxidized during the melting of the alloy blocks.
[0055] S4: The vacuum arc melting furnace is evacuated and filled with argon gas. First, the sponge titanium is melted. Then, the prepared alloy block is repeatedly melted 10 times before being removed to obtain a ceramic-toughened lightweight iron-based alloy.
[0056] Specifically, evacuating and purging a vacuum arc melting furnace with argon gas includes the following steps:
[0057] The mechanical pump and pre-evacuation valve of the vacuum arc melting furnace are turned on to evacuate the vacuum. When the vacuum level of the vacuum arc melting furnace drops to 5 Pa, the fore-stage valve, main evacuation valve, and molecular pump of the vacuum arc melting furnace are turned on in sequence to carry out the high vacuum process, and the vacuum level reaches 3.0 × 10⁻⁶ Pa. -3 When the vacuum level reaches -0.07 MPa, close the molecular pump and the main extraction valve. Open the charging valve to charge argon gas into the furnace. When the vacuum level of the vacuum arc melting furnace reaches -0.07 MPa, close the charging valve.
[0058] It should be noted that ceramic-toughened lightweight iron-based alloys can be prepared using elemental metals. However, due to the highly volatile nature of elemental manganese (Mn), using an Fe-50Mn master alloy can effectively reduce manganese volatilization. Introducing carbon during the smelting process is difficult. If graphite powder is used, it is easily sucked into the vacuum pump during vacuuming. Furthermore, graphite powder is prone to volatilization during smelting, and during carbonization reactions, it is more likely to form cementite in the alloy, leading to severe segregation. Therefore, a low-carbon Fe-5C alloy is used to introduce carbon.
[0059] Specifically, in step S4, each melting process involves moving the arc gun to the melting position. After successful arc ignition, the arc gun current is gradually increased by 50A each time, up to 550A. After all the ingredients have completely melted, the electromagnetic stirrer is turned on and stirred for 5 minutes. Then, the arc gun current is slowly and gradually reduced until it is turned off.
[0060] The method for preparing ceramic-toughened lightweight iron-based alloys in this embodiment can form large-sized test blocks with uniform microstructure and stable performance at the kilogram level, enabling them to be more widely used in diesel engine main fixed components (frame, base, main bearing, etc.), transmission components (connecting rod assembly, crankshaft, etc.), and combustion chamber components (cylinder head, cylinder and piston assembly).
[0061] The following are specific examples.
[0062] Example 1
[0063] A method for preparing a ceramic-toughened lightweight iron-based alloy includes the following steps:
[0064] (1) Weigh out a mixture of 3g nano AlN powder and 27g Al powder and 1.5g methanol and put it into a zirconia ball mill jar.
[0065] (2) Add 3mm, 5mm and 8mm zirconia grinding balls to the zirconia grinding jar respectively. The total mass of the zirconia grinding balls is 90g, and the mass ratio of the 3mm, 5mm and 8mm zirconia grinding balls is 2:2:1.
[0066] (3) After sealing the zirconia ball mill jar with an O-ring, the zirconia ball mill jar is evacuated and filled with argon gas. The mixture is ball-milled at a speed of 150 r / min for 3 h to obtain a uniformly mixed AlN / Al intermediate alloy composite powder.
[0067] (4) The AlN / Al master alloy composite powder was loaded into a graphite mold and sintered without pressure in a hot-press sintering furnace. After cooling to room temperature, the powder was removed and cut into blocks to obtain AlN / Al master alloy ingots. The sintering process was automatically heated from room temperature to 520°C with a heating current of 0.25 kA.
[0068] The sintering vacuum degree is 3 Pa. The automatic heating process is as follows: from room temperature to 100℃, the heating rate is 3℃ / min; from 100℃ to 400℃, the heating rate is 10℃ / min; from 400℃ to 480℃, the heating rate is 5℃ / min; from 480℃ to 520℃, the heating rate is 2℃ / min; and the temperature is held at 520℃ for 60 min. The size of the AlN / Al master alloy ingot is 5mm×5mm×3mm.
[0069] Specifically, in this embodiment, a hot pressing sintering furnace (ZT-40-20Y) produced by Shanghai Chenhua Electric Furnace Co., Ltd. is used as a vacuum electric arc melting furnace for sintering.
[0070] (5) Weigh out 100g of pure iron millimeter ingots with a purity ≥99%, Fe-50Mn centimeter ingots, pure aluminum millimeter ingots, pure nickel millimeter ingots, Fe-5C centimeter ingots, pure titanium millimeter ingots, and AlN / Al master alloy ingots in a ratio of 12.55:50:6.75:8:20:0.2:2.5 and place them in the first crucible position of the vacuum arc melting furnace. Then, put sponge titanium in the second crucible position of the vacuum arc melting furnace, evacuate the vacuum arc melting furnace and fill it with argon gas. First, melt the sponge titanium, and then repeatedly melt the prepared alloy blocks 10 times before taking them out to obtain ceramic toughened lightweight iron-based alloy.
[0071] Specifically, evacuating and purging a vacuum arc melting furnace with argon gas includes the following steps:
[0072] The mechanical pump and pre-evacuation valve of the vacuum arc melting furnace are turned on to evacuate the vacuum. When the vacuum level of the vacuum arc melting furnace drops to 5 Pa, the fore-stage valve, main evacuation valve, and molecular pump of the vacuum arc melting furnace are turned on in sequence to carry out the high vacuum process, and the vacuum level reaches 3.0 × 10⁻⁶ Pa. -3When the vacuum level reaches -0.07 MPa, close the molecular pump and the main extraction valve. Open the charging valve to charge argon gas into the furnace. When the vacuum level of the vacuum arc melting furnace is -0.07 MPa, close the charging valve. In step S4, the process of melting the prepared alloy blocks each time involves moving the arc gun to the melting position. After successful arc ignition, gradually increase the arc gun current by 50 A each time, up to 550 A. After all the ingredients have completely melted, turn on the electromagnetic stirrer and stir for 5 minutes. Then, slowly and gradually decrease the arc gun current until it is turned off.
[0073] In this embodiment, the iron-based alloy prepared by the above-mentioned method for preparing ceramic-toughened lightweight iron-based alloy is Fe-25Mn-9Al-8Ni-1C-0.2Ti-0.25AlN material, abbreviated as 0.25AlN iron-based alloy material. By mass percentage, the raw materials for synthesis consist of the following components: Mn: 25%, Al: 9%, Ni: 8%, C: 1%, Ti: 0.2%, AlN: 0.25%, with the balance being Fe and unavoidable impurities.
[0074] Example 2
[0075] The preparation method of Example 2 is basically the same as that of Example 1, except that the configuration ratio of pure iron millimeter ingots, Fe-50Mn centimeter ingots, pure aluminum millimeter ingots, pure nickel millimeter ingots, Fe-5C centimeter ingots, pure titanium millimeter ingots, and AlN / Al master alloy ingots is 12.3:50:4.5:8:20:0.2:5. The prepared iron-based alloy is Fe-25Mn-9Al-8Ni-1C-0.2Ti-0.5AlN material, abbreviated as 0.5AlN iron-based alloy material. By mass percentage, the raw materials are composed of the following components: Mn: 25%, Al: 9%, Ni: 8%, C: 1%, Ti: 0.2%, AlN: 0.5%, with the balance being Fe and unavoidable impurities.
[0076] Example 3
[0077] The preparation method of Example 3 is basically the same as that of Example 1, except that the configuration ratio of pure iron millimeter ingots, Fe-50Mn centimeter ingots, pure aluminum millimeter ingots, pure nickel millimeter ingots, Fe-5C centimeter ingots, pure titanium millimeter ingots, and AlN / Al master alloy ingots is 12.05:50:2.25:8:20:0.2:7.5. The prepared iron-based alloy is Fe-25Mn-9Al-8Ni-1C-0.2Ti-0.75AlN material, abbreviated as 0.75AlN iron-based alloy material. By mass percentage, the raw materials are composed of the following components: Mn: 25%, Al: 9%, Ni: 8%, C: 1%, Ti: 0.2%, AlN: 0.75%, with the balance being Fe and unavoidable impurities.
[0078] Example 4
[0079] The preparation method of Example 4 is basically the same as that of Example 1, except that the configuration ratio of pure iron millimeter ingots, Fe-50Mn centimeter ingots, pure aluminum millimeter ingots, pure nickel millimeter ingots, Fe-5C centimeter ingots, pure titanium millimeter ingots, and AlN / Al master alloy ingots is 11.80:50:0:8:20:0.2:10. The prepared iron-based alloy is Fe-25Mn-9Al-8Ni-1C-0.2Ti-1AlN material, abbreviated as 1AlN iron-based alloy material. By mass percentage, the raw materials are composed of the following components: Mn: 25%, Al: 9%, Ni: 8%, C: 1%, Ti: 0.2%, AlN: 1%, with the balance being Fe and unavoidable impurities.
[0080] Comparative Example 1
[0081] The preparation method of Comparative Example 1 is basically the same as that of Example 1, except that the key component AlN / Al master alloy ingot is omitted when melting pure iron millimeter ingots with a purity ≥99%, Fe-50Mn centimeter ingots, pure aluminum millimeter ingots, pure nickel millimeter ingots, Fe-5C centimeter ingots, pure titanium millimeter ingots, and AlN / Al master alloy ingots. The iron-based alloy obtained is 0AlN iron-based alloy material.
[0082] The specimens prepared using a 5504-GL electronic universal testing machine for the iron-based alloy materials obtained in Examples 1-4 and Comparative Example 1 had a size of 44 × 7 × 1.5 mm. 3 Room temperature tensile properties were tested on flat, dog-bone-shaped specimens with dimensions of 50 × 12 × 2 mm. 3 Flat, dog-bone-shaped specimens (with 6mm diameter holes at both clamping ends) were subjected to tensile tests at 600℃. The tensile rate was 1mm / min, and the entry force was 50N. At least three parallel specimens were tested for each material. Before testing, the surface of the tensile specimens was rough-ground and then fine-ground with sandpaper of different grits until no obvious scratches remained. The phase composition and microstructure of the materials were then characterized using a Bruker D2 PHASER Gen2 X-ray diffractometer, an Axio observer 7m fully automated inverted metallographic microscope, and a JEOL JEM-2010 transmission electron microscope. The results are as follows: Figures 2-5 As shown in Table 2.
[0083] Table 2 Comparison of density and mechanical properties at different temperatures of iron-based alloy materials prepared in Examples 1-4 and Comparative Example 1
[0084]
[0085] As shown in Table 2, the densities of the iron-based alloy materials prepared in Examples 1-4 and Comparative Example 1 are 6.48-6.54 g·cm³. -3 The room temperature tensile strength and elongation are 751.7–802.4 MPa and 22.1%–54.8%, respectively, with a room temperature strength-ductility product of 17.73–42.10 GPa·%. At 400℃, the tensile strength and elongation are 647.6–678.2 MPa and 18.8%–29.0%, respectively, with a strength-ductility product of 12.17–19.56 GPa·%. At 600℃, the tensile strength and elongation are 552.6–585.9 MPa and 9.9–20.1%, respectively, with a strength-ductility product of 5.64–11.37 GPa·%. It is evident that the ceramic-toughened lightweight iron-based alloy of this invention significantly improves both strength and elongation, achieving a good match between strength and toughness, solving the problem of the difficulty in achieving both strength and plasticity in cast iron alloys, and can be applied to the manufacture of diesel engines.
[0086] Depend on Figure 2 It can be seen that as the AlN content increases, the diffraction peaks of austenite in the alloy gradually strengthen, while the diffraction peaks of ferrite gradually weaken. This is because a small amount of AlN is added to the alloy, and the dispersed AlN in the alloy inhibits the nucleation of ferrite, thereby reducing the volume fraction of ferrite and thus lowering its diffraction peaks. At the same time, the volume fraction of austenite increases, which strengthens the diffraction peaks of austenite, further improving the plasticity of the alloy.
[0087] Depend on Figure 3 It can be seen that the microstructures of the iron-based alloy materials prepared in Example 2 and Comparative Example 1 are basically the same, mainly consisting of austenite and ferrite phases, with the matrix phase being austenite and the network-distributed phase being ferrite. (Comparison) Figure 3 (a) and Figure 3 (b) It can be seen that the metallographic structure of the alloy with added nano-AlN has finer grains than that of the alloy without added AlN.
[0088] Depend on Figure 4 It can be seen that the microstructure of the ceramic toughened lightweight iron-based alloy prepared in Example 2 mainly includes austenite phase, ferrite phase, TiC phase and AlN phase, among which the AlN phase exists stably in the material at the nanoscale and forms a good bond with the matrix.
[0089] Depend on Figure 5It can be seen that the room temperature tensile strength and elongation of the ceramic-toughened lightweight iron-based alloys prepared in Examples 1-4 and the iron-based alloy material prepared in Comparative Example 1 are 751.7-802.4 MPa and 22.1%-54.8%, respectively; the room temperature tensile strength and elongation are 647.6-678.2 MPa and 18.8%-29.0%, respectively; and the room temperature tensile strength and elongation are 552.6-585.9 MPa and 9.9-20.1%, respectively.
[0090] Analysis shows that by adding nano-sized AlN ceramic particles, the room temperature and high temperature mechanical properties of the ceramic-toughened lightweight iron-based alloy are significantly improved. In particular, the plasticity and strength-ductility product are nearly doubled while the strength is almost unchanged, solving the problem of existing iron-based alloys that struggle to achieve both room temperature and high temperature strength and plasticity. Compared with traditional materials used in diesel engine cylinder heads, the ceramic-toughened lightweight iron-based alloy prepared by this invention achieves a good balance between strength and toughness, solving the problem of cast iron alloys struggling to achieve both strength and plasticity, making it a potential material for next-generation, higher-power diesel engines.
[0091] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.
Claims
1. A method for preparing a ceramic-toughened lightweight iron-based alloy, characterized in that, The ceramic-toughened lightweight iron-based alloy is composed of the following components by mass percentage: Mn: 25%, Al: 9%, Ni: 8%, C: 1%, Ti: 0.2%, AlN: 0.1%~1%, with the balance being Fe and unavoidable impurities; A method for preparing the ceramic-toughened lightweight iron-based alloy includes the following steps: S1: Preparation of AlN / Al intermediate alloy composite powder; S2: The AlN / Al master alloy composite powder is loaded into a graphite mold and sintered in a hot-press sintering furnace without pressure. After sintering and cooling to room temperature, it is taken out and cut into blocks to obtain AlN / Al master alloy ingots. S3: Pure iron millimeter ingots with a purity ≥99%, Fe-50Mn centimeter ingots, pure aluminum millimeter ingots, pure nickel millimeter ingots, Fe-5C centimeter ingots, pure titanium millimeter ingots, and AlN / Al master alloy ingots are batched into alloy blocks according to a mass ratio of 11.80~12.55:50:0~6.75:8:20:0.2:2.5~10 and placed in the first crucible station of the vacuum arc melting furnace. Then, sponge titanium is placed in the second crucible station of the vacuum arc melting furnace. S4: Vacuum the vacuum arc melting furnace and fill it with argon gas. First, melt the sponge titanium, and then repeatedly melt the prepared alloy block 10 times before taking it out to obtain a ceramic-toughened lightweight iron-based alloy.
2. The method for preparing ceramic-toughened lightweight iron-based alloy according to claim 1, characterized in that, The preparation of AlN / Al master alloy composite powder includes: S11: Weigh a mixed powder consisting of nano AlN powder with a mass of M1 and Al powder with a mass of 9M1, and methanol with a mass of 0.5M1, and place it into a zirconia ball mill jar. S12: Add 3mm, 5mm and 8mm zirconia grinding balls to the zirconia grinding jar respectively, wherein the total mass of the zirconia grinding balls is 30M1, and the mass ratio of 3mm, 5mm and 8mm zirconia grinding balls is 2:2:1; S13: After sealing the zirconia ball mill jar with an O-ring, the zirconia ball mill jar is evacuated and filled with argon gas. The mixture is ball-milled at a speed of 150 r / min for 3 hours to obtain a uniformly mixed AlN / Al master alloy composite powder.
3. The method for preparing ceramic-toughened lightweight iron-based alloy according to claim 1, characterized in that, When AlN / Al master alloy composite powder is loaded into a graphite mold and sintered in a hot pressing sintering furnace, it is a vacuum pressureless sintering process. The sintering process is automatically heated from room temperature to 520°C, and the heating current is 0.25kA. The sintering vacuum degree is 3Pa~4Pa. The automatic heating process is as follows: from room temperature to 100℃, the heating rate is 3℃ / min; from 100℃ to 400℃, the heating rate is 10℃ / min; from 400℃ to 480℃, the heating rate is 5℃ / min; from 480℃ to 520℃, the heating rate is 2℃ / min; and the temperature is held at 520℃ for 60min. The AlN / Al master alloy ingot has a size of 5mm × 5mm × 3mm.
4. The method for preparing ceramic-toughened lightweight iron-based alloy according to claim 1, characterized in that, The process of evacuating and purging a vacuum arc melting furnace with argon gas includes the following steps: The mechanical pump and pre-evacuation valve of the vacuum arc melting furnace are turned on to evacuate the vacuum. When the vacuum level of the vacuum arc melting furnace drops to 5 Pa, the fore-stage valve, main evacuation valve, and molecular pump of the vacuum arc melting furnace are turned on in sequence to carry out the high vacuum process, and the vacuum level reaches 3.0 × 10⁻⁶ Pa. -3 When Pa is reached, shut off the molecular pump and the main extraction valve; Open the charging valve to charge argon gas into the furnace. When the vacuum degree of the vacuum arc melting furnace is -0.07 MPa, close the charging valve.
5. The method for preparing ceramic-toughened lightweight iron-based alloy according to claim 1, characterized in that, In step S4, the process of melting the prepared alloy block each time involves moving the arc gun to the melting position. After successful arc ignition, the arc gun current is gradually increased by 50 A each time, up to 550 A. After all the ingredients are completely melted, the electromagnetic stirring is turned on. After stirring for 5 minutes, the arc gun current is slowly and gradually reduced until it is turned off.
6. The application of the ceramic-toughened lightweight iron-based alloy prepared by the method of any one of claims 1 to 5 in a diesel engine.
Citation Information
Patent Citations
High-strength steel sheet and method for manufacturing same
CN107429355A
